Refined Analysis of the Correlation Between the Accepted Maximum Permissible Levels of Radio Frequency Electromagnetic Fields for the Population and the Lethality Rate of Covid-19 - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
In this paper, the results of a refined analysis of the correlation, previously discovered by the author, between the accepted maximum permissible levels (MPL) of radio frequency electromagnetic fields (RF EMF) for population and the mortality rate of COVID-19, carried out using the data samples from the World Health Organization (WHO), taken monthly from May 2020 to July 2021, are presented. To explain the results obtained, correlation between the accepted MPL for RF EMF, the level of vaccination of population against COVID-19, and the level of gross domestic product per capita in different countries were analyzed additionally. Analysis results confirm the presence of a noticeable correlation between the RF EMF MPLs and the COVID-19 mortality rate, especially in the first months of the analyzed period. The subsequent decrease in correlation between them by the end of analyzed period is a result of significantly larger efforts in struggle against COVID-19 in those countries where high RF EMF MPLs are adopted taking into account only the danger of thermal effects in human body, in comparison with countries where more stringent standards that take into account the danger of non-thermal bioeffects, are used. The first of these countries, having on average a higher level of economic development, ensured mass COVID-19 testing of population, imposition of tougher and longer restrictions (quarantines, lockdowns, etc.), as well as significantly higher rates of vaccination of the population. The presence of a confirmed correlation between these characteristics does not necessarily mean the existence of an unambiguous causal relationship between them. In countries of the first group with passive regulation of population protection from environmental factors, this principle is used not only in relation to RF EMF, but also in relation to the other factors. This determines the relevance of a deeper system analysis of the impact of the adopted legal systems for protecting the population from the entire set of anthropogenic factors on its health and collective immunity.